Pump-Free Microfluidic Rapid Mixer Combined with a Paper-Based Channel - Jang, Ilhoon; Carraõ, Daniel B.; Menger, Ruth F.; Moraes De Oliveira, Anderson R. [UNESP]; Henry, Charles S. (American Chemical Society (ACS), 2020)
Capillary forces are commonly employed to transport fluids in pump-free microfluidic platforms such as paper-based microfluidics. However, since paper is a porous material consisting of nonuniform cellulose fibers, it has some limitations in performing stable flow functions like mixing. Here, we developed a pump-free microfluidic device that enables rapid mixing by combining paper and plastic. The device was fabricated by laminating transparency film and double-sided adhesive and is composed of an overlapping inlet ending in a paper-based reaction area. The mixing performance of the developed device was confirmed experimentally using aqueous dyes and pH indicators. In addition, the absolute mixing index was evaluated by numerically calculating the concentration field across the microfluidic channels. To demonstrate the utility of the new approach, the detection of an organophosphate pesticide was carried out using a colorimetric enzymatic inhibition assay. The developed device and a smartphone application were used to detect organophosphate pesticide on food samples, demonstrating the potential for onsite analysis.
Keywords: capillary-driven microfluidic; colorimetric enzymatic inhibition assay; onsite analysis; passive mixer; pesticide